Colonial policing and police administration in erstwhile Northwest Frontier Province and tribal areas of British India - Farhat Ullah (Cogent Social Sciences, 2024)
Police were utilised in British India to put down resistance to colonial rule. The role of the police varied from region to region. This article discusses the style of policing and police administration designed by the British administrators in the province of erstwhile Northwest Frontier Province (Presently Khyber Pakhtunkhwa Province of Pakistan) and tribal areas adjacent to the province. Internal security was enforced by the police within the provinces, supplementing military efforts. Instead of using direct coercion, colonial authorities in the northwest frontier and border regions focused on integrating local populations into the system of regional security and coordinating their interests with those of the ruling class. The analysis in this article is based on the Indian archival records in the British Library London and other primary sources available in archives. This analysis demonstrates the importance of understanding colonial policing and police administration in the erstwhile Northwest Frontier province and tribal region near the border between British India and Afghanistan in particular leading to the postcolonial police administration in the northwestern frontier province of present-day Pakistan.